Pengaruh Personal Selling, Harga Terhadap Kepuasan Pelanggan Mulia Gold Palembang - Putri, Martha Bella Chandra; Megawati, Megawati (MDP Student Conference, 2024)
The aim of this research is to measure influence Personal Selling, Price on Customer Satisfaction Mulia Gold Palembang. This research is quantitative research using the previous measurement scale. The population in this research is consumers of the Mulia Gold Palembang Jewelry Shop in 2022, namely 600 consumers with a sample size of 100 respondents. The data source used is primary data obtained from the results of distributing questionnaires to respondents and secondary data used is in the form of the profile, history and organizational structure of Mulia Gold Palembang Jewelry Shop. The results of this research show that the variables Personal Selling and Price influence Customer Satisfaction at the Mulia Gold Palembang Jewelry Store.